AN ANALYSIS OF CONVERSATIONAL IMPLICATURE IN A FAMILY OF MANADO MALAY SPEAKERS: A CASE STUDY AT BULAWAN VILLAGE, KOTABUNAN SUB DISTRICT, KABUPATEN BOLAANG MONGONDOW TIMUR - Rizka Muslim; Theresye Wantania; Oldie S. Meruntu (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
The purpose of this research is to describe the form of premise conversational implicature and conclusion conversational implicature in Manado Malay-speaking families. In addition, this study aims at describing the meaning of those premise conversational implicature and conclusion conversational implicature. This study is conducted at Bulawan village, Kotabunan sub-district, Bolaang Mongondow Timur Regency. The method used in this research is descriptive qualitative method. To collect the data, the techniques used were the chirp method, the listening method and the note-taking method. The primary data of this research is obtained through conversational implicature in Manado Malay-speaking families in Bulawan village, Kotabunan sub-district, Bolaang Mongondow Timur Regency which amounted to at least 5 families. To analyze the data, the technique used is content analysis technique. The findings show that the conversational implicature used by Manado Malay speakers in Bulawan Village, Kotabunan Sub-district, Bolaang Mongondow Timur Regency is generally a concluding conversational implicature of 70%. The other 30% use premise implicature.